Efimbriate, herbaceous aristolochias in brazil and northwest south america (1977)
In this paper, four species of Aristolochia are taxonomically revised for Brazil, Colombia and Venezuela: they are treated as a unit because they are the only herbaceous, efimbriate, perennial species native to this region. Described in the literature as more than a dozen taxa, they have never been comprehensively reviewed as a unit before. Our treatment includes full synonymy,specimens studied, discussions of relationships and maps of known distributions utilizing materials loaned to us by more than 35 herbaria.